P033 The assessment of serum cytokines at baseline could predict mucosal healing in patients with Crohn's disease treated with ustekinumab. A prospective study. (30th January 2023) - Bertani, L; Antonioli, L; Fornili, M; D'Antongiovanni, V; Coppini, F; Ceccarelli, L; Carmisciano, L; Benvenuti, L; Mumolo, M G; Bottari, A; Baglietto, L; Bellini, M; et al.
Abstract: Background: Ustekinumab (UST) is a monoclonal IgG1 antibody binding the p40 subunit of IL-12 and IL-23. The blockage of the activation of the heterodimer IL-12/IL-23 inhibits the differentiation of Th1 and Th17 cells, reducing the inflammatory cascade typical of Crohn's disease (CD). Some patients with CD achieve mucosal healing after one year of UST therapy, whereas others experience primary non-response or loss of response. No biomarkers are currently available to predict therapeutic response to UST. The aim of this prospective study was to identify one or more biomarkers able to predict mucosal healing in patients with CD treated with UST. Methods: We prospectively enrolled all consecutive CD patients treated with UST, following the current guidelines. A blood sample was drawn before UST infusion at week 0 (baseline), 24 and 48, and serum cytokines IL1α, IL-1β, IL-6, IL-8, IL-10, IL-12, IL-13, IL-15, IL-17, IL-22, IL-23 and IL-33 were evaluated by a fluorescence assay. At the same timepoints, Fecal Calprotectin (FC) was assessed. A colonoscopy was performed before starting the treatment and at week 48, where therapeutic outcome was evaluated in terms of mucosal healing, defined as a Simple Endoscopic Score for CD <2. Results: Out of 44 patients enrolled, 22 (50%) achieve mucosal healing at the end of follow up. Baseline IL-23 levels were higher in responders than in non-responders (Mann-Whitney test, p-value<0.001), whereas higher baseline levels of IL-1α are associated with non-response (p=0.03). We also observed a higher probability of mucosal healing in those with lower levels of IL-6 at baseline (p=0.05). A borderline statistically significant association was observed for baseline FC, which values were lower in responders than in non-responders (Mann-Whitney test, p=0.098). No significant differences were observed with regard to the baseline levels of the other cytokines. FC levels decreased over time in responders, whereas its values did not change over time in non-responders (test for the interaction between time and outcome, p<0.001). IL-13 presented a homogenously decreasing time trend regardless the outcomes (test for the association with time and outcome, p=0.019). No significant time trend was observed with regard to the other cytokines. Conclusion: Baseline serum levels of IL-23, IL-1α and IL-6, as well as the decrease of FC over time, showed a good reliability in predicting therapeutic outcome to UST in CD in terms of mucosal healing. These biomarkers could help clinicians in the perspective of a better management of UST therapy, identifying early the patients with higher probability to respond to the treatment.